Analysing the Behaviour of Soil Reinforced with Polyethylene Terephthalate (PET) Plastic Waste - Luwalaga, John Groover. (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.